2023
DOI: 10.1002/jcv2.12196
|View full text |Cite
|
Sign up to set email alerts
|

Sustained improvements by behavioural parent training for children with attention‐deficit/hyperactivity disorder: A meta‐analytic review of longer‐term child and parental outcomes

Dominique P. A. Doffer,
Tycho J. Dekkers,
Rianne Hornstra
et al.

Abstract: BackgroundBehavioural parent training is an evidence‐based intervention for children with attention‐deficit/hyperactivity disorder (ADHD), but little is known about the extent to which initial benefits are maintained.AimsThis meta‐analytic review investigated longer‐term (i.e., more than 2 months post‐intervention) child and parental outcomes of behavioural parent training for children with ADHD.Materials & MethodsWe searched for randomized controlled trials and examined ADHD symptoms, behavioural problems… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The pooled data set also does not contain any objective measures of children’s interpersonal behaviors, and it may be that parents’ program engagement influences their ratings of children’s interpersonal conflict. However, a recent meta-analysis of behavioral parent training programs (Doffer et al, 2023) found that effect sizes on child behavior obtained through independent observations did not differ from those obtained through parent report.…”
Section: Discussionmentioning
confidence: 96%
“…The pooled data set also does not contain any objective measures of children’s interpersonal behaviors, and it may be that parents’ program engagement influences their ratings of children’s interpersonal conflict. However, a recent meta-analysis of behavioral parent training programs (Doffer et al, 2023) found that effect sizes on child behavior obtained through independent observations did not differ from those obtained through parent report.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, commercialized BPT and homegrown BPT have been found to be effective in improving the functioning of children with ADHD and their parents [ 14 16 ]. A recent meta-analysis also suggests sustained benefits of BPT over the course of a year on child ADHD symptoms, parenting behavior, parenting sense of competence and parental mental health [ 17 ]. The significance of BPT should be, however, put into a broader context to appreciate the clinical benefits of this intervention.…”
Section: Efforts At Improving Efficacy and Effectiveness Of Psychosoc...mentioning
confidence: 99%
“…These programs, known as parent training, aim to enhance parenting skills and foster healthier parent-child relationships, thus leading to improved behavioral outcomes in children (Grolnick et al, 2009;Lundahl et al, 2006;Sanders et al, 2012). Parent trainings have been considered a best evidence-based practice in treating a range of childhood disorders, including autism (Byrne et al, 2023;Deb et al, 2020;Lichtle et al, 2020;Tabatabaei et al, 2022), attention deficit hyperactivity disorder (Doffer et al, 2023;Lee et al, 2022;Marquet-Doléac et al, 2024), disruptive behavior disorders (Beelmann et al, 2023;Bloss et al, 2022;Zarakoviti et al, 2021), and emotion-regulation problems (Zalewski et al, 2020). Despite their established efficacy, parent training interventions have not been systematically deployed to specifically target or prevent behavioral issues related to children's engagement with technologies, such as screen time management and online safety (Danet, 2020), and their application in this field thus remains largely unexplored (Saccà et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%